Peran Corporate Social Responsibility Bank Indonesia dalam Pengembangan Usaha Pertanian Pondok Pesantren Babakan Jamanis - Daris Susanto (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Babakan Jamanis Islamic Boarding School has developed an agricultural programme that aims to improve santri's knowledge in agriculture. With the construction of the Greenhouse, it is hoped that santri will not only understand religious knowledge, but also be able to develop agriculture in their respective areas after they return home. This programme is a strategic step to create independent santri and contribute to the development of local agriculture, so as to improve community welfare. The research method used in this study is a qualitative approach, which involves collecting primary and secondary data through interviews, observation, and documentation. This research focuses on the Agricultural Management at Pondok Pesantren Babakan Jamanis as the research subject. Data analysis techniques are carried out systematically to understand the meaning of the data obtained, with the aim of providing a clear picture of the sustainability of the agricultural business being run. The results showed that Bank Indonesia's Corporate Social Responsibility (CSR) programme had a significant positive impact on the development of agricultural businesses at the Babakan Jamanis Islamic Boarding School. Through the assistance of modern agricultural facilities and infrastructure, as well as training to increase the capacity of human resources, this programme has helped farmers improve agricultural efficiency and productivity. Thus, this initiative has not only reduced dependence on human labour, but also significantly increased crop yields, contributing to the sustainability of the farming business in the pesantren.